The search for optimal competitive balance in formula one - Thomas Krauskopf; Martin Langen; Björn Bünger (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
In this paper an analysis of the determinants of attractiveness of the Formula One is attempted. Therefore the concept of competitive balance will be explained and applied. The principal item of this analysis will be the result that there is an optimal level of competitive balance which maximizes the attractiveness. This concept will be applied through an empirical analysis of the determinants of the German Formula One number of TV viewers. It is shown that the influence of competitive balance is not totally clear. A too high level of competitive balance seems to be as detrimental as a too low level of competitive balance.
Keywords: L83; 330; Sports Economics; Formula 1; competitive balance; attractiveness of sports